1998
DOI: 10.1034/j.1600-0420.1998.760113.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface and environmental changes

Abstract: ABSTRACT.Purpose: To investigate if ocular surface and precorneal tear film are influenced by the environment. Method: We studied the environmental influences on the ocular surface using the tests Break-up time, Schirmer-1 test and Rose Bengal staining. We correlated the values of the above tests among three groups of normal people from different places in Greece with different climates and levels of atmospheric pollution. Group A consisted of 57 persons coming from an area with a dry and warm climate and heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 4 publications
2
34
0
3
Order By: Relevance
“…In another study, an increase in relative humidity from 35% to 43% had no effect on break-up time (self-reported), although the perception that the air was dry was reduced significantly (75). It has been found that break-up time is lower in dry and warm environments than in cold and humid ones (57). Similarly, break-up time was inversely associated with increasing temperature among female nurses, in addition to dust settlement rate (possibly a proxy for airborne particles), and urban vicinity (traffic-related pollution) (58).…”
Section: Destabilization Of Tear Filmmentioning
confidence: 96%
“…In another study, an increase in relative humidity from 35% to 43% had no effect on break-up time (self-reported), although the perception that the air was dry was reduced significantly (75). It has been found that break-up time is lower in dry and warm environments than in cold and humid ones (57). Similarly, break-up time was inversely associated with increasing temperature among female nurses, in addition to dust settlement rate (possibly a proxy for airborne particles), and urban vicinity (traffic-related pollution) (58).…”
Section: Destabilization Of Tear Filmmentioning
confidence: 96%
“…If more than one factor is involved, depending upon their characteristics they may interact at lower threshold values and induce EDED. Accordingly, the detrimental effects of environmental toxic agents on EDED epidemiology are not entirely understood (43,44,(60)(61)(62) . The impact of urban pollution and environmental toxins on the ocular surface has been evaluated in a few case-control studies.…”
mentioning
confidence: 99%
“…Although there is increasing awareness of postoperative dry eye syndrome [15] the preoperative evaluation is still not sufficiently standardized in order to establish successful preoperative treatment of tear fluid insufficiencies prior to surgery both in cataract [15], glaucoma and laser surgery. Preoperative surface alterations will enhance the likelihood of postoperative dry eye complaints and changes when they combine with peri-operatively introduced known DED triggering factors such as mechanical forces aging, thermic and phototoxic effects and chemical toxicity of glaucoma treatment [16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%